Determination Of 137CS In Batam Water As South China Sea Extention Using Ammonium Phospomolibdate (AMP) Method - Wahyu Retno Prihatiningsih; Heny Suseno; Murdahayu Makmur; Untara Untara; Abarrul Ikram; Mohamad Nur Yahya; Yogi Priasetyono; Deddy Irawan Permana Putra (Jurnal Segara, 2021)
A Study of the Characteristics of the 137Cs of the South China Sea in Batam Waters has been carried out. The South China Sea through several straits is connected to the Pacific Ocean region and the Indonesian Sea. The mass of Pacific water entering the South China Sea will reach Batam Waters with radioactive contaminants. Batam Waters are part of the Karimata Strait which is the Extention Line of South China Sea so that it has the potential to receive 137Cs of radioactive contaminants from operational nuclear reactors discharged in the coastal regions of China. The purpose of the study is to find out the characteristics of 137Cs and obtain the current status of 137Cs as a baseline to minimize the impact of nuclear activities on the ecosystem of the waters of Batam, Indonesia. The 137Cs characterization method uses the Ammonium Phosphomolibdate (AMP) with modification of base dissolution and measurement validation with Certified Reference Material (CRM). The results of monitoring the concentration of 137Cs in seawater in Batam waters are in the range <0.03 - 0.35 ± 0.02 Bq.m-3, while the concentration of 137Cs activity in Batam waters sediments is known to be a maximum of 0.22 ± 0.08 Bq.kg-1 with 134Cs below MDA. Result in seawater and sediments are comparable to previous research related to the presence of radiocesium in the region